Gamification of production and logistics operations: Status quo and future directions - Warmelink Harald; Koivisto Jonna; Mayer Igor; Vesa Mikko; Hamari Juho (Elsevier Inc., 2022)
This article presents a review of the current body of academic literature concerning gamification of production and logistics to understand the status quo and provide suggestions for future research. The findings indicate that the execution and control of production and logistic processes has been addressed most often in the current body of literature, which mostly consists of design research. Objectives and goals, points, achievements, multimedial feedback, metaphorical or fictional representations, and levels and progress are currently the most often employed affordances within this field. Research has focused in the given context on examining or considering motivation, enjoyment and flow, as the main psychological outcomes of gamification, while individual performance and efficiency are the most commonly examined or suggested behavioral and organizational impacts. Future studies should employ more rigorous designs within new subdomains of production and logistics and should firmly ground research designs and discussions in management theory and critical studies.